Risk-takers : alcohol, drugs, sex, and youth - Plant, Martin A.; Plant, Moira (London ; New York : Tavistock/Routledge, 1992)
Annotation Gives a comprehensive view of youthful involvement with drinking, smoking, illicit drug use and sexual activity, providing a challenging assessment of health education for young people.
1. The causes of drug use -- 2. Drinking habits -- 3. Smoking habits -- 4. Illicit drug use -- 5. Alcohol misuse -- 6. Tobacco-related harm -- 7. Drug-related harm -- 8. Alcohol, drugs and pregnancy -- 9. Sexual behaviour -- 10. Alcohol, drugs and risky sex -- 11. Risk-takers -- 12. Prevention and harm minimization -- 13. Conclusions.
Includes bibliographical references (pages 144-166) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Teenagers -- Great Britain; Risk-taking (Psychology) in adolescence -- Great Britain; Teenagers -- Sexual behavior -- Great Britain; Teenagers -- Alcohol use -- Great Britain; Teenagers -- Drug use -- Great Britain; Drinking of alcoholic beverages; Risk-taking (Psychology); Drug addiction; Drug abuse; Adolescent Behavior; Alcohol Drinking; Adolescent; Risk-Taking; Sexual Behavior; Substance-Related Disorders -- epidemiology; Substance-Related Disorders; United Kingdom; Adolescents -- Grande-Bretagne.; Prise de risque chez l'adolescent -- Grande-Bretagne.; Adolescents -- Sexualité -- Grande-Bretagne.; Adolescents -- Consommation d'alcool -- Grande-Bretagne.; Consommation d'alcool.; Prise de risque; Toxicomanie; drug abuse; drug addiction; FAMILY & RELATIONSHIPS -- Life Stages -- Adolescence; FAMILY & RELATIONSHIPS -- Life Stages -- Teenagers; Risk-taking (Psychology); Drug addiction; Drug abuse; Drinking of alcoholic beverages; Risk-taking (Psychology) in adolescence; Teenagers; Teenagers -- Alcohol use; Teenagers -- Drug use; Teenagers -- Sexual behavior; Great Britain; Jugend; Sexualverhalten; Risikoverhalten; Drogenkonsum; Großbritannien; Adolescents; Great Britain